Leveraging blockchain technology for carbon footprint information sharing - Shuhua Zhang; Wen Liu; Pengwen Hou (Blockchain)
This paper investigates the information sharing strategies of green supply chains, greenwashing, and blockchain technology. The unobservable green activities in the manufacturing process references to those aspects of logistics activities that are imperceptible to consumers. To ensure that consumers perceive authentic green information without being influenced by greenwashing, the retailer and manufacturer can collaborate on establishing a blockchain platform for sharing the manufacturer’s carbon footprint data. The research findings indicate that the manufacturer may be motivated to share its carbon footprint information to stimulate consumer demand for green products. Additionally, the retailer may proactively invest in constructing a blockchain platform to facilitate the sharing of the manufacturer’s carbon footprint data and enhance sales profitability. Analysis indicates that when consumers possess a higher anticipated level of unobservable greenness and exhibit greater sensitivity to green issues, there is an enhanced motivation for both manufacturers and retailers to implement blockchain technology. Interestingly, due to the construction costs associated with implementing the blockchain platform, the manufacturer and retailer are more likely to collaborate on this endeavor. However, this shift in the information sharing structure benefits all members of the supply chain, resulting in a mutually beneficial outcome. Furthermore, the dominant blockchain strategy is influenced by factors such as cost and market strategy.